Academic freedom, integrity and research ethics (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The limits, purpose and scope of academic freedom have been the subject of media controversy, partly because academic freedom and academic integrity are close relatives, the occasional missing link being research ethics. While freedom and integrity should protect each another, it is difficult for institutions and those who navigate them to balance competing and conflicting demands. Some of these demands are at the institutional level and others at the individual level. The purpose of this paper is to tease out some of the issues which are often too sensitive to articulate in the public square.